Diverse subducted sediments and ambient mantle wedge heterogeneity caused spatiotemporal variations in the composition of gabbroic rocks in the Gangdese Batholith, southern Tibet - Rui-Qiang Wang; Jian-Sheng Qiu; Ding-Jun Wen; Timothy Chapman; Ying Xia; Yue Chen (Lithos, 2026)

Activity, Ranging, and Habitat Use Patterns of Two Groups of Boutourline’s Blue Monkeys (Cercopithecus mitis boutourlinii) in Habitats with Different Levels of Anthropogenic Modification in Hamuma Coffee Forest, Ethiopia - Meseret Chane; Afework Bekele; Peter J. Fashing; Colin A. Chapman; Dereje Yazezew; Hussein Ibrahim; Amera Moges; Nga Nguyen; Timothy M. Eppley; Vivek V. Venkataraman; Addisu Mekonnen (International Journal of Primatology, 2026)

Heterospecific social behavior in primates: insights into the evolutionary roots of pet-keeping - Cyril C. Grueter; Fany Roncin; K. Anne-Isola Nekaris; Jill Pruetz; Richard McFarland; Sabit Hasan; Malgorzata Arlet; Timothy M. Eppley; Susan M. Cheyne; Vincent Nijman; Eckhard W. Heymann; Pascal R. Marty; et al. (Primates, 2026)
Primate interspecific interactions with both other primates and non-primate species range from predator–prey dynamics to affiliative behaviors such as grooming, play, and carrying. While many primates participate in interspecific associations or commensal relationships, to our knowledge interspecific social interactions have never been systematically synthesized. Here, we present the first comprehensive review of such interactions, compiling 427 cases from the literature, media sources, and a global survey of primatologists. These involved 88 primate species and 127 non-primate species (including mammals, birds, reptiles, amphibians, malacostracans, and insects) across wild (n = 311) and captive (n = 111) contexts. The most frequent interactions occurred within or between primate families (e.g., Cercopithecidae–Cercopithecidae, Cebidae–Atelidae), though affiliative behaviors were also directed toward distantly related taxa such as dogs and birds. Play (n = 139) and grooming (n = 136) were most common. Juveniles and infants predominantly engaged in play, while adult females were more likely to groom. Adult males were less affiliative overall. Contrary to expectations, affiliative behaviors were not more often directed toward immature than adult heterospecifics. Primates were the initiators in most interactions. These findings offer new insights into the diversity and contexts of heterospecific sociality in primates and suggest that some behavioral tendencies relevant to later forms of human–animal companionship – such as caregiving, tolerance, and exploratory play – may be more widespread among primates than previously recognized.

Dietary exposure and health risk assessment of metals in fish and shellfish from five markets in Southern Nigeria - Chinelo Nzekwe; Deborah V. Chapman; Alex Okoro; Israel Ikoyi; Timothy Sullivan (Food and Chemical Toxicology, 2025)

Predicting run-of-mine diamond price using size frequency populations and price modelling - John G. Chapman; Timothy E. Chapman (Mineralogy and Petrology, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Magmatic flare-ups in arcs controlled by fluctuations in subduction water flux - Timothy Chapman; Luke A. Milan; Sabin Zahirovic; Andrew S. Merdith; Geoffrey L. Clarke; Mingdao Sun; Nathan R. Daczko (Tectonophysics, 2024)

Late Cretaceous bimodal volcanic rocks in Shuanghu induced by lithospheric delamination beneath the Southern Qiangtang, Tibet - Ding-Jun Wen; Xiumian Hu; Timothy Chapman; Gang Zeng; An-Lin Ma; Rui-Qiang Wang (Lithos, 2023)

Endothelial Rbpj Is Required for Cerebellar Morphogenesis and Motor Control in the Early Postnatal Mouse Brain - Amelia D. Chapman; Samantha Selhorst; Julia LaComb; Alexis LeDantec-Boswell; Timothy R. Wohl; Subhodip Adhicary; Corinne M. Nielsen (The Cerebellum, 2022)

Attentional focus does not impact locomotor–respiratory coupling in trained runners - Abigail S. L. Stickford; Jonathon L. Stickford; Timothy J. Fulton; Taylor L. Lovci; Robert F. Chapman (European Journal of Applied Physiology, 2020)

Applying citizen science to monitor for the Sustainable Development Goal Indicator 6.3.2: a review - Lauren Quinlivan; Deborah V. Chapman; Timothy Sullivan (Environmental Monitoring and Assessment, 2020)

Japan’s mega solar boom: quantifying social equity expectations and realities at the local scale - Andrew Chapman; Timothy Fraser (Sustainability Science, 2019)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Subduction initiation and ophiolite crust: new insights from IODP drilling - Mark K. Reagan; Julian A. Pearce; Katerina Petronotis; Renat R. Almeev; Aaron J. Avery; Claire Carvallo; Timothy Chapman; Gail L. Christeson; Eric C. Ferré; Marguerite Godard; Daniel E. Heaton; Maria Kirchenbaur; et al. (International Geology Review, 2017)

Endurance exercise performance in acute hypoxia is influenced by expiratory flow limitation - Joshua C. Weavil; Joseph W. Duke; Jonathon L. Stickford; Joel M. Stager; Robert F. Chapman; Timothy D. Mickleborough (European Journal of Applied Physiology, 2015)

Operating lung volumes are affected by exercise mode but not trunk and hip angle during maximal exercise - Joseph W. Duke; Jonathon L. Stickford; Joshua C. Weavil; Robert F. Chapman; Joel M. Stager; Timothy D. Mickleborough (European Journal of Applied Physiology, 2014)

Continuous high-frequency monitoring of estuarine water quality as a decision support tool: a Dublin Port case study - Ciprian Briciu-Burghina; Timothy Sullivan; James Chapman; Fiona Regan (Environmental Monitoring and Assessment, 2014)

Increases in $$ \dot{V} $$ O2max with “live high–train low” altitude training: role of ventilatory acclimatization - Daniel P. Wilhite; Timothy D. Mickleborough; Abigail S. Laymon; Robert F. Chapman (European Journal of Applied Physiology, 2013)

NMR q-space analysis of canonical shapes of human erythrocytes: stomatocytes, discocytes, spherocytes and echinocytes - Timothy J. Larkin; Guilhem Pages; Bogdan E. Chapman; John E. J. Rasko; Philip W. Kuchel (European Biophysics Journal, 2013)

Shallow Water '06: A Joint Acoustic Propagation/Nonlinear Internal Wave Physics Experiment - Dajun Tang; James Moum; James Lynch; Phil Abbot; Ross Chapman; Peter Dahl; Timothy Duda; Glen Gawarkiewicz; Scott Glenn; John Goff; Hans Graber; John Kemp; et al. (Oceanography, 2007)